The Right and the good. - Ross, David (Oxford University Press, 2002)
The Right and the Good, a classic of twentieth-century philosophy by the great scholar Sir David Ross, is now presented in a new edition with a substantial introduction by Philip Stratton-Lake, a leading expert on Ross. Ross's book is the pinnacle of ethical intuitionism, which was the dominant moral theory in British philosophy for much of the nineteenth and early twentieth century. Intuitionism is now enjoying a considerable revival, and Stratton-Lake provides the context for a proper understanding of Ross's great work today.